2011
DOI: 10.3348/kjr.2011.12.5.559
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between Benign and Malignant Solid Thyroid Nodules Using an US Classification System

Abstract: ObjectiveTo evaluate the diagnostic accuracy of a new ultrasound (US) classification system for differentiating between benign and malignant solid thyroid nodules.Materials and MethodsIn this study, we enrolled 191 consecutive patients who received real-time US and subsequent US diagnoses for solid thyroid nodules, and underwent US-guided fine-needle aspiration. Each thyroid nodule was prospectively classified into 1 of 5 diagnostic categories by real-time US: "malignant," "suspicious for malignancy," "borderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 26 publications
1
42
1
2
Order By: Relevance
“…17,23 However, this study showed the diagnostic accuracy of US for thyroid nodules on a larger scale, correlated these with histopathologic results, and attempted to use a different US classification system for solid nodules versus PCTNs. The diagnostic accuracies for nodules in SN-US class I, SN-US class II, SN-US class III, SN-US class V, PCTN-US class I, and PCTN-US class IV are considerably higher than those for SN-US class IV, PCTN-US class II, and PCTN-US class III.…”
Section: Discussionmentioning
confidence: 99%
“…17,23 However, this study showed the diagnostic accuracy of US for thyroid nodules on a larger scale, correlated these with histopathologic results, and attempted to use a different US classification system for solid nodules versus PCTNs. The diagnostic accuracies for nodules in SN-US class I, SN-US class II, SN-US class III, SN-US class V, PCTN-US class I, and PCTN-US class IV are considerably higher than those for SN-US class IV, PCTN-US class II, and PCTN-US class III.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this imaging modality aids the decision-making processes of which nodules to target for fine needle aspiration biopsy (FNAB) and increases the diagnostic yield of thyroid cell sampling (Perros et al 2014, American Cancer Society 2015, Pitoia & Miyauchi 2015. Multiple studies have confirmed typical sonographic features associated with increased risks of (Table 2) (Frates et al 2005, Hambly et al 2011, Lee et al 2011, and current guidelines now recommend the use of a combination of these features in algorithms predicting the likelihood of thyroid malignancy as well as the selection of nodules requiring FNAB (Perros et al 2014, Haugen et al 2015, Pitoia & Miyauchi 2015. Highresolution ultrasonography by an experienced operator is highly recommended in the initial evaluation of patients with thyroid nodules.…”
Section: Current Diagnostic Approaches and Limitationsmentioning
confidence: 99%
“…However, as evidenced by several large-scale studies (24,25,26,27,28,29,30,31,32,33), certain US features appear reliably associated with a higher risk for malignancy in thyroid nodules (2). A taller-than-wide shape and centrifugal growth across the tissue planes are indicators of malignancy.…”
Section: Reliability Of Us Criteria For Malignancymentioning
confidence: 99%